Empowering mātauranga Māori to transform our understandings of freshwater management : a thesis presented in partial fulfilment of the requirements for the degree of Master's of Science in Ecology at Massey University, Palmerston North, New Zealand - Rangiwananga, Natalia Helene Ramari Areta (Massey University, 2020)
Mātauranga Māori is a rich, complex knowledge system that informs kaitiaki and positions tangata whenua within the living system that is our whenua and wai. However, the underlying assumptions of colonial frameworks conflict with Te Ao Māori because they privilege economic growth, situate people as separate from land, and understand land as an ownable resource. I draw upon the concept of incommensurability to portray how globally dominant frameworks privilege western understandings throughout all societal structures of Aotearoa, continuing to marginalise indigenous peoples and their knowledge. I identify how these systemic effects impact mana whenua ability to carry out kaitiakitanga of waterways, and how these effects work to keep us disconnected from our whenua which is an integral aspect to our identity and realisation of cultural kawa and tikanga. The Macroinvertebrate Community Index is a method scientists use to assess the health of waterways; this and other western tools are useful mechanisms to monitor the states of our waterways and generate knowledge. There are overlaps in conclusions drawn from MCI results and the Wai Ora Wai Māori tool in assessments of the Turitea and Mahuraunui streams, such as a positive relationship between native riparian forest and stream health. However, policies and scientific monitoring privilege western frameworks, which creates inadequate representation of Māori values in freshwater management. I suggest that our understandings of waterways as ‘resources to be managed’ needs to change so that we can draw from multiple baskets of knowledge; so communities can direct kaitiakitanga of their local wai and whenua; and so economic development can be viewed as an extra benefit to increasing the hauora of people and whenua, rather than being the driver of our behaviour. Decolonisation at the structural level is critical to the future health of our whenua and society. Mātauranga-led collaborations at the local scale can create social movement to contribute to decolonisation of social structures at national and global scales. Transformations in Ecology can also enable researchers to recognise how community values influence their research so they may become culturally, politically, and ethically motivated in their work.
Keywords: 450999 Ngā mātauranga taiao o te Māori kāore anō kia whakarōpūtia i wāhi kē (Māori environmental knowledges not elsewhere classified)